Dynamic carrier transports and low thermal conductivity in n‐type layered InSe thermoelectrics. Issue 4 (24th June 2021) - Shi, Haonan; Wang, Dongyang; Xiao, Yu; Zhao, Li‐Dong
Abstract: Semiconductor InSe with wide bandgap and layered crystal structure is expected to be a promising thermoelectric material, and its excellent plasticity brings great potential applications in flexible and wearable thermoelectric devices. To advance its thermoelectric performance, this work systematically investigates the carrier and phonon transport properties in n ‐type InSe. It is found that InSe compound presents an exceptional dynamic carrier transport property due to the amphoteric indium (In + and In 3+ ), which contributes to favorable temperature‐dependent increasing carrier concentration. More importantly, with S alloying in InSe, the carrier concentration can be further enhanced from ∼3.2 × 10 13  cm –3 in InSe to ∼4.8 × 10 15  cm –3 in InSe0.97 S0.03 at 300 K, because S ( χ P  ∼ 2.58) with larger Pauling electronegativity than Se ( χ P  ∼ 2.55) can induce more In 3+ state to increase carrier concentration in matrix. This boosted dynamic carrier transport property benefits an obviously enhanced power factor. Additionally, InSe compound presents intrinsically low thermal conductivity ∼1.6 W m –1  K –1 at 300 K due to low‐symmetry crystal structure and strong anharmonicity. This work indicates that the special dynamic carrier transport property and intrinsically low thermal conductivity in InSe make it as a worth‐expecting thermoelectric material. Abstract : InSe compound is crystalized in low‐symmetry layered crystal structure with a space group of P63 /mmc, which causes strong anharmonicity and intrinsic low lattice thermal conductivity. Besides, the amphoteric indium (In + and In 3+ ) in InSe contributes to an exceptional dynamic carrier transport property. Furthermore, S alloying in InSe can induce more In 3+ states in matrix due to the larger Pauling electronegativity of S ( χ P ∼ 2.58) than Se ( χ P ∼ 2.55), which can largely boost dynamic carrier concentration and finally benefit an obviously enhanced power factor. This work not only proves the potential thermoelectric performance in InSe but also provides an effective strategy of electronegativity manipulation to optimize the thermoelectric materials.